Temporal dynamics of summer phytoplankton communities and their response to environmental changes in the northern Yellow Sea (2011-2020) - Yibo Wang; Yibo Wang; Zhiliang Liu; Zhiliang Liu; Yanping Qi; Yang Chen; Yang Chen; Haibo Zhang; Xihan Liu; Xihan Liu; Du Su; Du Su (Frontiers in Marine Science)
Research on phytoplankton distribution and dynamics is crucial for understanding marine ecosystem functions and evaluating their status. The northern Yellow Sea (NYS), a marginal sea of the Pacific Ocean, has experienced significant anthropogenic impacts since the late 20th century, resulting in an increased nitrogen-to-phosphorus (N/P) ratio and heightened phosphorus limitation. These changes are considered critical factors affecting the phytoplankton community structure in the NYS over recent decades. This study analyzed the temporal dynamics of environmental factors and phytoplankton community structure in the NYS during the summers from 2011 to 2020, aiming to elucidate recent changes in phytoplankton community structure and their driving forces. The results indicated a significant decrease in dissolved inorganic nitrogen (DIN) concentration after 2011, resulting in a decreased N/P ratio, while phosphorus limitation persisted. Temperature, temperature gradient (reflecting stratification intensity) and salinity exhibited upward trends, whereas pH, nitrogen-to-silicon (N/Si) ratio, and chlorophyll-a concentration showed downward trends. The abundances of total phytoplankton, Bacillariophyta, and Dinoflagellata, as well as the Dia/Dino index, fluctuated annually and correlated with temperature, temperature gradient, and nutrient structure. Diversity indices remained stable throughout the study period. The Yellow Sea Cold Water Mass prominently influenced summer phytoplankton community structure, exhibiting lower phytoplankton abundance, Dia/Dino index, and species richness in the cold water mass region, where adaptable species such as Tripos muelleri and Paralia sulcata predominated. Our results emphasized the impact of environmental changes associated with climate change, including rising temperatures, increased salinity, and enhanced stratification, on the phytoplankton community structure in recent years, particularly concerning the dominant species composition and the Dia/Dino index. Therefore, ongoing attention to the effects of climate change on coastal environments and phytoplankton communities is essential.